2009
DOI: 10.1111/j.1551-2916.2009.03239.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkali Elements Content on the Structure and Electrical Properties of (K0.48Na0.48Li0.04)(Nb0.90Ta0.04Sb0.06)O3 Lead‐Free Piezoelectric Ceramics

Abstract: In this communication, we report on the effects of alkaline elements (K, Na, and Li) content on the electrical properties of (K0.48Na0.48Li0.04)(Nb0.90Sb0.06Ta0.04)O3 ceramics. Because of the high volatility, the alkaline elements evaporate during the high‐temperature sintering process, generating vacancy defects in the ceramics. As a result, the ferroelectric and piezoelectric properties of the ceramics become weakened. Our results reveal that the volatilization loss can be effectively compensated by a 1 mol%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…4a, two dielectric peaks for the ceramics with x = 0 are observed at 62 and 328°C, respectively. Our previous studies have confirmed that the first peak (T O-T ) at 62°C is ascribed to the transition from orthorhombic to tetragonal phase, while the second peak T C at 328°C is related to that from cubic to orthorhombic phase [11]. As shown in Fig.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…4a, two dielectric peaks for the ceramics with x = 0 are observed at 62 and 328°C, respectively. Our previous studies have confirmed that the first peak (T O-T ) at 62°C is ascribed to the transition from orthorhombic to tetragonal phase, while the second peak T C at 328°C is related to that from cubic to orthorhombic phase [11]. As shown in Fig.…”
Section: Introductionsupporting
confidence: 75%
“…for A-sites ions and/or B-sites ions [8][9][10]. Our previous study has shown that the (K 0.48 Na 0.48 Li 0.04 ) (Nb 0.90 Ta 0.04 Sb 0.06 )O 3 ceramic exhibits excellent ferroelectric and piezoelectric properties because of the coexistence of orthorhombic and tetragonal phases [11]. On the other hand, with the rapid development of electronic/microelectromic devices towards miniaturization and multifunctionalization, multifunctional materials have attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Our research indicated that the KNN-(Bi 0.5 Na 0.5 )TiO 3 ceramics with small amounts of LiSbO 3 exhibited the excellent piezoelectric properties when 1 mol% (Bi 0.5 Na 0.5 )TiO 3 was added. Many researches have been focused on the KNN-LiSbO 3 systems [17][18][19][20][21]. But few reports are involved with the solid solutions of K 0.5 Na 0.5 NbO 3 -Bi 0.5 Na 0.5 TiO 3 -LiSbO 3 system, and the effect of LiSbO 3 on the properties of the K 0.5 Na 0.5 NbO 3 -Bi 0.5 Na 0.5 TiO 3 -LiSbO 3 ceramics remains unclear.…”
Section: Introductionmentioning
confidence: 95%
“…Although the maximum dielectric constant at the Curie temperature (ε m ) for K2NN is quite low, ε m increased markedly with increasing BaTiO 3 content. K2NNBT10 ceramics has the largest ε m (>10,000) which is even higher than that of doped K 0.5 Na 0.5 NbO 3 ceramics [4,5]. Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Different dopants are studied to improve their piezoelectric properties, including Li + , Ta 5+ , Sb 5+ , Bi(Zn 0.5 Ti 0.5 )O 3 , BaTiO 3 , etc. [4][5][6][7][8]. BaTiO 3 modified K 0.5 Na 0.5 NbO 3 ceramics were studied by many researchers.…”
Section: Introductionmentioning
confidence: 99%